Cross-Cultural Household Influence on Vaccination Decisions. (October 2016) - Taylor, Eric; Atkins, Katherine E.; Medlock, Jan; Li, Meng; Chapman, Gretchen B.; Galvani, Alison P.
Uptake of vaccination against seasonal influenza is suboptimal in most countries, and campaigns to promote vaccination may be weakened by clustering of opinions and decisions not to vaccinate. This clustering can occur at myriad interacting levels: within households, social circles, and schools. Given that influenza is more likely to be transmitted to a household contact than any other contact, clustering of vaccination decisions is arguably most problematic at the household level. We conducted an international survey study to determine whether household members across different cultures offered direct advice to each other regarding influenza vaccination and whether this advice was associated with vaccination decisions. The survey revealed that household members across the world advise one another to vaccinate, although to varying degrees, and that advice correlates with an increase in vaccination uptake. In addition, respondents in Japan, China, and the United States were less likely to offer advice to older adults than to the young, despite older adults' being the target age group for vaccination in both Far Eastern countries. Furthermore, advice was not primarily directed to household members within the age groups advised to vaccinate by national health policies. In Japan, advice was offered more to ages outside of the policy guidelines than inside. Harnessing the influence of household members may offer a novel strategy to improve vaccination coverage across cultures worldwide.